Evaluation of the Anticarcinogenic and Cytotoxicity Effects of Small Gold Nanorods Against Gliomablast Cell Lines in an In vitro Model - Ozer, S.; Kelleci, K.; Canim-Ates, S.; Canbek, C. (Current Analytical Chemistry, 2025)
Objectives The study aimed to evaluate the cytotoxicity and anticancer potential of gold nanorods (GNRs) synthesized using hexadecyltrimethylammonium bromide capped seed (CTAB) on L929 fibroblast cells and glioma cells. Methods Gold nanorods were synthesized through the CTAB method, and their characterization was conducted using UV-Vis spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), and scanning electron microscopy (SEM). The MTT cell viability assay was employed to assess the cytotoxic and anticancer effects of the synthesized gold nanorods on L929 fibroblast cells and glioma cells. Results Analysis results revealed that the synthesized gold nanorods had an average size of 6.4 nm and rod-like morphology, with an absorbance peak of 836 nm. The quantity of synthesized GNRs was calculated to be 3.63 µM. Cytotoxicity analysis showed an IC50 value of 1.29 µM for L929 fibroblast cells and 1.26 µM for C6 glioma cells, indicating significant cytotoxic effects. Treatment with GNRs induced apoptosis in glioma cells and inhibited their proliferation, suggesting potential anticancer activity. Conclusion The findings suggest that GNRs hold promise as effective agents for cancer therapy. Further research is warranted to elucidate the precise mechanisms underlying their anticancer effects and to explore their potential clinical applications in cancer treatment.
Keywords: glioma cancer